Penerapan Metode Composite Performance Index Dalam Sistem Pendukung Keputusan Untuk Menentukan Penerima Zakat Studi Kasus Baznas Provinsi Bengkulu - Wawan Alfarizi; Siswanto Siswanto; Dewi Suranti (UNIVED Press, 2024)
Zakat is one of the pillars of Islam that must be fulfilled and some muzaki entrust the distribution of zakat to National Zakat Agency (BAZNAS). Zakat collected at BAZNAS is then distributed to mustahik (zakat recipients) who have the right according to the applicable sharia provisions. Problems arise when in determining the suitability of potential recipients because the number is large and widespread over a certain period of time, requiring accuracy in selection. In this research, a decision support system was built to select potential recipients using the composite performance index method. The data used are criteria and sub-criteria, as well as potential recipients (alternative data). The criteria used are four criteria: residence, income, employment status, number of dependents, based on the results of research conducted by the writer.